Effect of Nanofilled Resin-Based Coating on the Compressive Strength of Glass Ionomer Cement – in vitro - Ardy Setiawan; Juanita Amaludin Gunawan; Selviana Wulansari; Didi Nugroho (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Glass ionomer cement as one of the restoration materials requires high compressive strength so it can last during functional activity. The latest glass ionomer cement comes with glass hybrid technology and a nanofilled resin-based protective coating which is said to increase the compressive strength of glass ionomer cement. The aim of this study was to analyze the effect of nanofilled resin-based coating and the types of glass ionomer cement materials on their compressive strength. Two types of commercial glass ionomer cement material were used; conventional (Fuji IX GP Extra), and hybrid (EQUIA Forte Fill) glass ionomer cement. Forty cylindrical (4 x 6 mm) samples were prepared in each group. The main group was divided into 4 subgroups (n=10) based on the protective coating used (EQUIA Forte Coat, Varnish, Control, Water + EQUIA Forte Coat). Eight subgroups were immersed in 37 °C distilled water for 7 days, then a compressive strength test was performed using a universal testing machine. The data analysis showed no significant difference in the compressive strength between the two types of glass ionomer cement materials (p>0.05). The use of a protective coating was associated with a significant decrease in the compressive strength (p<0.05). The use of glass ionomer cement without the application of a protective coating was considered to be quite good because the compressive strength value of the restoration still met the standards of the American Dental Association.